2009
DOI: 10.1097/tp.0b013e3181a5e034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Pretransplant Donor-Specific HLA Antibodies Detected by Single-Antigen Flow-Beads

Abstract: These results support the utility of SAFB for pretransplant risk assessment and organ allocation, and suggest that improvement of the positive predictive value of HLA-DSA defined by SAFB will require an enhanced definition of pathogenic factors of HLA-DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
189
5
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(221 citation statements)
references
References 26 publications
(29 reference statements)
22
189
5
5
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] These studies were excluded from our primary analysis. A quantitative analysis of this cohort (group 2) was limited to eight studies because adequate data could not be extracted from one of the studies identified for inclusion in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] These studies were excluded from our primary analysis. A quantitative analysis of this cohort (group 2) was limited to eight studies because adequate data could not be extracted from one of the studies identified for inclusion in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in pretransplant period, determination of clinically relevant alloantibodies in sensitized patients and monitoring of antibody level during desensitization treatment would be needed. But in posttransplant period, although there are significant amount of evidences for the causal effect of DSA in graft rejection, the uniform consensus or guidelines for immune monitoring is hard to be set up partly because the lack of validated therapy once DSA are detected in a clinically and pathologically stable patient and vice versa (21)(22)(23)(24) and partly because the lack of data whether low level of DSA or anti-allelic DSA cause graft dysfunction (25,26) The study was performed by questionnaire surveys through emailing. The questionnaires were developed in two (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 30 out of the 67 patients who had anti-HLA DSA did not have a clinical/subclinical antibody mediated rejection [28]. Five-year death censored graft survival among this group was similar to the transplant patients without anti-HLA DSA.…”
Section: Significance Of Donor Specific Antibodiesmentioning
confidence: 96%
“…In one study that investigated DSA in over 400 transplant recipients, those with preformed anti-HLA DSA had inferior graft survival at 8 years as compared with those with no preformed DSA (93% vs. 61%) [27]. Another study investigated pre-transplant DSA in 334 patients and found a higher incidence of clinical/subclinical antibody mediated rejection in those with DSA (55% vs. 6%) [28]. The strength of the DSA as measured by MFI may also play a role in the development of antibody mediated rejection [27].…”
Section: Significance Of Donor Specific Antibodiesmentioning
confidence: 99%